Silas Deane papers - Deane, Silas, 1737-1789.
Letters to Deane from Benjamin Franklin, account kept while in France (1776-1781), certificate of appointment as an American representative in France, and papers relating to Deane's financial claims against Congress (1775-1777).
In part, photocopies.
Member of the Continental Congress from Connecticut and diplomat.
Collection material in English.
Keywords: Franklin, Benjamin, -- 1706-1790 -- Correspondence; France -- Foreign relations -- United States; United States -- Foreign relations -- France; United States. -- Continental Congress; Diplomatic and consular service, American -- France; Delegates, U.S. Continental Congress -- Connecticut; Diplomats